Table of Content - - (Journal of Humanities & Social Sciences, 2025)
Table of Content:The scientific life of the city of Levantine Tripoli during the nineteenth century ADMr. Abdallah Samir DannounChildren in Difficult Situations: Between the Challenges of Reality and the Possibilities  of Integration Sociological study/Guercif -Morocco-Dr. Abdelillah DouzLearning Difficulties and their Realtionship with Family Systems(Bent Jbail region-southern Lebanon 2018) Mr. Daoud Ali FarajFamily in search of a treatment: Example of Families facing infertility in the city of Tetouan, northern Morocco (2023–2024)Asst-Prof. Mohamed Ahmed NFIFAKHThe Impact of Overlooking the Social Dimension in Urban Projects on Citizens’ Behavior  Toward Public Property: A Case Study of Kenitra CityMr. Mohamed EL Mestari, Dr. Mbarek TayiiTraditional Tanning Craft in Buraidah City during (1322-1402AH/1904-1982AD)Mr. Abdulkarim Mohammad Alseadoon,Co-Prof. Soliman Mohammed Al-Atni
Keywords: Journal of Human and Social Sciences